Geriatric assessment in the older adult with genitourinary cancer: A narrative review - Singhal, Surbhi; Marwell, Julianna G.; Khaki, Ali Raza (Frontiers in Oncology, 2023)
Genitourinary (GU) cancers including bladder, prostate, and kidney cancers affect older adults with a higher prevalence compared to younger adults. GU cancer treatment is associated with poorer outcomes in older adults compared to their younger counterparts. To better identify and support older adults receiving cancer care, oncologic societies recommend the use of a geriatric assessment (GA) to guide management. However, little is known about the implementation and usefulness of the GA in older adults with GU cancers. We performed a narrative review to investigate the utility of the GA in older adults with GU cancers and propose strategies to optimize the real-world use of the GA. Here, we describe a framework to incorporate GA into the routine cancer care of older adults with GU cancers and provide several implications for future research.